On the road to systemic sustainability : how can cleantech facilitate the Finnish sustainability transition - a multi-layer perspective backcasting analysis - Laitinen, Jarno P. (2015)
Sustainable development has been a dominant theme in international debate since inception. During the last decades it has gained momentum due to pressing challenges in the domains of agriculture, energy, transportation, raw materials, water and ecosystems. Finland ranks highly on many sustainable development benchmarks, but the success is imbalanced. For constructing long-term redundant sustainability and well-being, Finland needs a transition affecting policy, people and businesses. This study has an intertwined theoretical and applied objective, following a pragmatist approach. The theoretical objective is to develop a conceptual framework for analysing future oriented sustainability transition processes. The conceptual framework constructs sustainability as a property of complex systems and describes ontology of sustainable development through human-nature and socio-technical systems. Change is seen as a socio-technical transition process, and described through multi-layer perspective framework. The applied objective is to use normative fore- and backcasting scenario analysis within the framework for describing the present state of sustainable development within Finland and for envisaging a roadmap for the needed sustainability transition process from perspective of cleantech industry as a key facilitator. The study validates both the conceptual framework and analytical methods for describing and analysing future oriented sustainability transitions. The analysis results in a description of a transition space and a roadmap for cleantech to facilitate the Finnish sustainability transition. As conclusions and summary of the analysis the study presents ten strategic ‘clean-steps’ to transition.